The therapeutic potential of mesenchymal stromal cells in the treatment of chemotherapy-induced tissue damage - Rühle, Alexander; Lopez Perez, Ramon; Huber, Peter E.; Nicolay, Nils (Stem cell reviews and reports, 2019)
Chemotherapy constitutes one of the key treatment modalities for solid and hematological malignancies. Albeit being an effective treatment, chemotherapy application is often limited by its damage to healthy tissues, and curative treatment options for chemotherapy-related side effects are largely missing. As mesenchymal stromal cells (MSCs) are known to exhibit regenerative capacity mainly by supporting a beneficial microenvironment for tissue repair, MSC-based therapies may attenuate chemotherapy-induced tissue injuries. An increasing number of animal studies shows favorable effects of MSC-based treatments; however, clinical trials for MSC therapies in the context of chemotherapy-related side effects are rare. In this concise review, we summarize the current knowledge of the effects of MSCs on chemotherapy-induced tissue toxicities. Both preclinical and early clinical trials investigating MSC-based treatments for chemotherapy-related side reactions are presented, and mechanistic explanations about the regenerative effects of MSCs in the context of chemotherapy-induced tissue damage are discussed. Furthermore, challenges of MSC-based treatments are outlined that need closer investigations before these multipotent cells can be safely applied to cancer patients. As any pro-tumorigenicity of MSCs needs to be ruled out prior to clinical utilization of these cells for cancer patients, the pro- and anti-tumorigenic activities of MSCs are discussed in detail.